2016
DOI: 10.3109/0886022x.2016.1172928
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in treatment and diagnosis of forgotten/encrusted double-J ureteral stents: the largest single-center experience

Abstract: Forgotten/encrusted DJS may lead to complications in a range of urinary system infections, up to a loss of renal function. They can be safely and successfully removed, and the renal function can be preserved by endourologic techniques, starting with the least invasive procedures in centers highly experienced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…cutaneous surgery, ureteral and renal lithotripsy, or even nephrectomies (6)(7)(8). Lam et al analyzed 26 forgotten catheters and showed that it was necessary the use of 2.7 procedures to resolve the situation (9).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…cutaneous surgery, ureteral and renal lithotripsy, or even nephrectomies (6)(7)(8). Lam et al analyzed 26 forgotten catheters and showed that it was necessary the use of 2.7 procedures to resolve the situation (9).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Other associated factors are urinary sepsis, history of lithiasis, chemotherapy, pregnancy, chronic renal disease, and metabolic or congenital diseases. 20,22 The best way to prevent a US from incrustation, is to remove it as soon as it is no longer necessary, and to change the US every two to four months if the patient requires permanent use. 20 The treatment for incrustation is endourological, but requires experience because there is no consensus or an algorithm to manage this complication.…”
Section: Incrustationmentioning
confidence: 99%
“…Ahallal et al 20 consider that the best management for a small percentage of incrusted USs, in patients with good renal function, is the extracorporeal lithotripsy (EL), which enables the spontaneous release of small fragments. Adanur et al, 22 in a case series of 44 patients with incrusted USs, initiated the management with EL in 18 of them: in 5 of the patients the US removal could be easily performed via direct cystoscopy; the rest of them required other endourological procedures for the extraction of the US. Five cases required cystolithotripsy due to the incrustation of the distal part of the US.…”
Section: Incrustationmentioning
confidence: 99%
See 1 more Smart Citation
“…8 There are no algorithmic approaches in urology guidelines for forgotten stents in both adults and children, meaning their treatment may be complicated and difficult for urologists. 10 Therefore, the rationale of this study was to assess the causes of forgotten DJS and to devise a management plan for them.…”
Section: Introductionmentioning
confidence: 99%